A Novel System for the Synthesis of 2-Aminobenzthiazoles using Sodium Dichloroiodate - Telvekar, Vikas N.; Bachhav, Harshal M.; Bairwa, Vinod Kumar (Synlett, 2012)
2-Aminobenzthiazole is a privileged scaffold with a range of biological activities. However, to date, an efficient protocol for the synthesis of this ring system using aniline as a starting material has been lacking. Herein, for the first time, we describe a highly efficient and mild protocol for the synthesis of 2-aminiobenzthiazole using NaICl2.
Keywords: synthetic methods; oxidative cyclization; sodium dichloroiodate; aniline; aminobenzthiazole